A Survey on Salvia L. Taxa Distributed in Mardin Province - MUNGAN KILIÇ, Fatma (MAS Journal of Applied Sciences, 2022)
In this study, the morphological features, habitat areas and danger categories of 10 taxa (Salviasect.: S. macrochlamys Boiss. & Kotschy, S. trichoclada Bentham, S. suffruticosa Montbret & Aucher exBenth., S. bracteata Banks & Sol.; Hymenosphace sect.: S. multicaulis Vahl; Aethiopis sect.: S. syriacaL., S. montbretii Bentham, S. palaestina Bentham, Salvia brachyantha subsp. brachyantha (Bordz.)Pobed.; Hemisphace sect.: S. russellii Bentham) belonging to 4 sections of the genus Salvia distributed inMardin between 2018-2020, were examined. Plants generally spread on serpentine soils, roadsides andslopes. According to the Red Book of Plants of Turkey and IUCN 2001 risk categories, all taxa arewidely distributed (LC). All of the identified taxa are elements of the Irano-Turanian phytogeographicregion. This study will contribute to the recognition, protection of Tukey’s biological richness and to otherstudies on the subject.